Long-Horizon Mean-Reverting Stock Prices Revisited - McQueen, Grant (Journal of Financial and Quantitative Analysis, 1992)
This paper reexamines long-horizon stock returns and finds that previous work overstates the evidence of mean reversion. The overstatement is largely due to the implicit weighting of ordinary least-squares tests, which place more weight on the Depression and World War II observations, which have both large error variances and stronger mean-reverting tendencies. Additionally, the reliance on asymptotic statistics and the improper focus on only the most negative estimates of mean reversion contribute to the overstatement. Using generalized least-squares randomization tests on the 1926 to 1987 period, the random walk cannot be rejected for value- or equally-weighted real returns at any of 10 return horizons or by joint tests over all 10 horizons simultaneously. Additionally, the random walk cannot be rejected for the extended 1871 to 1987 period.